2016
DOI: 10.1158/0008-5472.can-15-2882
|View full text |Cite
|
Sign up to set email alerts
|

RARγ Downregulation Contributes to Colorectal Tumorigenesis and Metastasis by Derepressing the Hippo–Yap Pathway

Abstract: The Hippo-Yap pathway conveys oncogenic signals, but its regulation during cancer development is not well understood. Here, we identify the nuclear receptor RARg as a regulator of the Hippo-Yap pathway in colorectal tumorigenesis and metastasis. RARg is downregulated in human colorectal cancer tissues, where its expression correlates inversely with tumor size, TNM stage, and distant metastasis. Functional studies established that silencing of RARg drove colorectal cancer cell growth, invasion, and metastatic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…1G). Further, we found that TPA was able to shuttle YAP from the nucleus, where YAP exerts its major function on tumorigenesis38, to the cytoplasm (Fig. 1H); these effects were also dose-dependent, suggesting YAP can be directly inhibited by TPA.…”
Section: Resultsmentioning
confidence: 81%
“…1G). Further, we found that TPA was able to shuttle YAP from the nucleus, where YAP exerts its major function on tumorigenesis38, to the cytoplasm (Fig. 1H); these effects were also dose-dependent, suggesting YAP can be directly inhibited by TPA.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, several studies have confirmed that the mRNA levels of Yap (and TAZ) sufciently correlate with target gene expression and are significantly associated with cancer progression [7, 23]. Meanwhile, an increasing number of studies have also shown that Yap has the ability to interact with tumor suppressors in the cytoplasm [52], supporting the idea that excessive expression of Yap is actually a more important factor in tumorigenesis regardless of Yap nuclear localization or cytoplasmic retention [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Yap has 504 amino acids (aa), including an N-terminal TEAD-binding domain (TBD, 48-102 aa), a WW domains (WW, 171-263 aa) and a C-terminal transcriptional activation domain (TAD, 292-488 aa) [38]. Therefore, three types of YAP mutants were constructed via base deletion to generate mutant-Yap (102-504 aa), which lacks the TBD, mutant-Yap (263-504 aa), which lacks the TBD and WW, and mutant-Yap (1-263 aa) , which lacks the TAD according to a previous study [8]. For lentiviral packaging, the three PCR-amplified mutant Yaps were cloned into pCMV vectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Kaplan-Meier analysis, we indicated that nuclear YAP expression in the cancerous tissues correlated positively with lymph node metastasis, which might support the hypothesis that YAP can be used as a potential marker for tumor invasiveness. 23 We examined the expression levels of the WASF1 gene and found that they were downregulated following YAP knockdown In summary, we demonstrated that YAP was overexpressed in OSCC, notably in the nuclear region and that it promoted tumor migration and invasiveness. It is important to note that silencing of YAP was able to inactivate WAVE1, which reduced cell migration and invasion.…”
Section: Discussionmentioning
confidence: 84%